2(x-2)+2=x+1 2(x-2)-3(4x-)=9(1-x) 7(2x-1)-3(4x-1)=4(3x+2)-1
1个回答
(1) 2x-4+2=x=1
2x-x=1+2
x=3
(2) 2x-4-12x=9-9x
-x=13
x=-13
(3) 14x-7-12x+3=12x+8-1
-10x=11
x=-11/10
相关问题
(3x^2+9x+7)/(x+1)-(2x^2+4x-3)/(x-1)-(x^3+x+1)/(x^2-1)=
(3x^2+9x+7)/(x+1)-(2x^2+4x-3)/(x-1)-(x^3+x+1)/(x^2-1)=
解线性方程组(1)2x1-x2+x3-2x4=7 (2)x1+2x2-3x3=-4 (3)-x1-x2+x3+4x4=4
线性方程组为:x1-x2-5x3+4x4=2 2x1-x2+3x3-x4=1 3x1-2x2-2x3+3x4=3 7x1
(x1-x2+4x3-2x4=0;x1-x2-x3+2x4=0;3x1+x2+7x3-2x4=0;x1-3x2-12x3
3道解方程1.2(2-x)+3(4x-2)=7(x+4)2.2(x-2)+3(2x-1)=9(x-1)3.10*(2-x
研究下列算式:4x1x2=3^2-1,4x2x3=5^2-1,4x2x4=7^2-1,4x4x5=9^2-1,4x5x6
已知方程(1)3x-1=2x+1,(2)3/2x-1=x,(3)x+1/3=2/3x-2,(4)7/2+1+3x/4=7
解方程.(1)[9x+7/3x+2-4x+52x+3]=1(2)[x-2/x+2-1=16x2-4].
巧算(3x^2+9x+7)/(x+1)-(2x^2-4x-3)/(x-1)-(x^2+x+1)/(x^2-1)